Traffic Capacity Assessment of the Selected Track Section on the Slovak Railways Network after the Implementation of ETCS L3 Based on Signaling Principle - Dedik, Milan; Stefancova, Vladimira; Gasparik, Jozef; Luptak, Vladimir; Vojtek, Martin (MDPI, 2022)
In the field of railway operation, it is essential to establish uniform conditions for interconnectivity requirements and compatibility of equipment in the Pan-European railway area to ensure effective interoperability. It also includes, for example, the introduction of a control system with modern and advanced interlocking systems (safety devices). The European Train Control System (ETCS) is a single European train protection system that will increase safety in rail transport. Nevertheless, this system may have an impact on the throughput on those railway lines where it is applied. The main research objective is to determine the impacts and effects of the configuration of track signaling equipment on the operational management of traffic and especially on the creation of a traffic plan. The optimization of transport processes on the railway infrastructure means creating the conditions for achieving higher throughput performance, especially including a higher number of train paths into the train traffic diagram. This paper examines and compares the impacts of ETCS and its levels (in particular ETCS L3) on the practical throughput of the selected national infrastructure manager. A heuristic procedure is used with the application of the analytical methodology of the Railways of the Slovak Republic (ZSR), which uses the principles of mathematical statistics and probability. Significant comparative indicators are occupancy times and the degree of utilization of practical throughput. These are used in investment decisions in the modernization of line sections to achieve interoperability of the railway system.
Posouzení kapacity vybraného úseku tratě na síti Železnic Slovenské republiky po implementaci ETCS L3
Keywords: capacity assessment; European train control system; track section; practical throughput; posouzení kapacity; evropský vlakový zabezpečovač; traťový úsek; praktická propustnost